An analysis of risk factors for visceral disseminated varicella in children - Guo, Shuai; Guo, Qin; Wan, Chaomin (Frontiers in Pediatrics, 2024)
Background Visceral disseminated varicella involves the internal organs, and complications such as encephalitis, hepatitis, and coagulation disorders threaten a patient's life. In this study, our aim is to analyze the risk factors for visceral disseminated varicella to enable the early identification of patients at a high risk of visceral disseminated varicella. Methods We reviewed the medical records of children hospitalized with varicella. The data covered demographics, clinical manifestations, auxiliary examinations, treatments, and outcomes. Logistic regression was used to analyze the risk factors. Results A multivariate logistic regression analysis showed that abdominal pain [odds ratio (OR) 20.451, 95% CI 1.637–255.548], increased levels of C-reactive protein (OR 12.794, 95% CI 1.820–89.937), increased levels of alanine aminotransferase (OR 7.453, 95% CI 1.624–34.206), and the time between onset and antiviral therapy of more than 7 days (OR 12.451, 95% CI 1.569–98.810) were independent risk factors for visceral disseminated varicella. Conclusions Patients with varicella who have the abovementioned risk factors need to be monitored for the risk of developing visceral disseminated varicella, for which timely antiviral therapy is necessary.